Pengembangan Produk Pangan (Camilan) Dan Minuman Sebagai Upaya Dalam Membangun Perekonomian Asosiasi TPQ Di Pondok Pesantren Darussalam Blokagung - Susanti, Nawal Ika; Ekaningsing, Lely Ana Ferawati; Insaniyah, Anyes Lathifatul (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this service is to be able to improve the services of the TPQ Association by developing various food and beverage products and providing entrepreneurship training to Santri at Darussalam Blokagung Islamic Boarding School. The method used in this service uses the ABCD method. The result of this dedication is that students develop food products, namely snacks and drinks. Some of these snack and beverage products are obtained from the results of collaboration with partners who provide raw materials for these food and beverage products and some are the result of developments carried out by the santri. In this service, the tyim also provides insightful knowledge about entrepreneurship by conducting training for students for entrepreneurship to marketing the products they develop to compiling simple financial reports. This service activity can be realized 80%. This is because some of the obstacles faced by students, namely the time used to be able to do entrepreneurship is limited. However, this does not make the students give up and give up on learning entrepreneurship in the Islamic boarding school environment.